A Note on the Exact Green Function for a Quantum System Decorated by Two or More Impurities - Glasser, M. L. (Frontiers in Physics, 2019)
The exact Green function is constructed for a quantum system, with known Green function, which is decorated by two delta function impurities. It is shown that when two such impurities coincide they behave as a single singular potential with combined amplitude. The results are extended to N impurities.